Cochrane Database of Systematic Reviews 2012
DOI: 10.1002/14651858.cd007731.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum(Reishi mushroom) for cancer treatment

Abstract: placebocontrolled, multicenter study of Ganoderma lucidum (w.curt.:fr.) Lloyd (aphyllophoromycetideae) polysaccharides (ganopoly) in patients with advanced lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
53
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 28 publications
0
53
1
2
Order By: Relevance
“…The Cochrane collaboration presented by Jin et al (2012) also reviewed the benefit of lingzhi in terms of cancer treatment. They summarized that the evidence of using lingzhi as a first line treatment for cancer was insufficient to prolong long term survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Cochrane collaboration presented by Jin et al (2012) also reviewed the benefit of lingzhi in terms of cancer treatment. They summarized that the evidence of using lingzhi as a first line treatment for cancer was insufficient to prolong long term survival.…”
Section: Discussionmentioning
confidence: 99%
“…They summarized that the evidence of using lingzhi as a first line treatment for cancer was insufficient to prolong long term survival. However, it could be administered as an alternative adjunct to conventional treatment for enhancing tumor response and stimulating host immunity (Jin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this treatment remains ineffective due to its toxicity to normal cells (2). Natural medicine has been widely used for treating malignant tumors for thousands of years (3,4). There is great potential in identifying drugs from natural medicine for the treatment of metastatic breast cancer due to their wide range of biological activities and low toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…A scientific review has indicated that the Ganoderma mushroom produces beneficial effects as an adju-vant agent for cancer treatment. 13) In addition, G. lucidum also improves the quality of life [the International Prostate Symptom Score (IPSS)] of men who have lower urinary tract symptoms. 14) To date, pharmacologically active compounds from the Ganoderma species have been found to be polysaccharides and triterpenes.…”
mentioning
confidence: 99%